An Efficient Synthesis of a Highly Functionalized Dihydrobenzothiophene Derivative: A Ring-Contracted Analogue of the Anti-inflammatory Drug Propoxicam - Tenti, Giammarco; Clerigué, José; Ramos, M. Teresa; Menéndez, J. Carlos (Synlett, 2022)
A five-step route to a ring-contracted analogue of the oxicam derivative propoxicam from thiosalicylic acid, sarcosine and N,N-dimethyl-1,3-propanediamine is described. The route has as key steps the base-promoted cross-Claisen coupling of protected sarcosine and thiosalicylic acid derivatives, the installation of a β-ketoamide moiety and a final Hg(II)-induced cyclization that creates the C–S bond of the benzothiophen-3-one core.
Keywords: oxicam; benzotriazole activation; cross-Claisen coupling; β-ketoamide synthesis; benzothiophene synthesis; domino reactions